2017
DOI: 10.1590/0104-07072017000260016
|View full text |Cite
|
Sign up to set email alerts
|

Dispositivo Educação Em Saúde: Reflexões Sobre Práticas Educativas Na Atenção Primária E Formação Em Enfermagem

Abstract: Objective: to construct reflections on the health education device, considering the educational health practices developed in the Primary Health Care and in the nursing training.Method: this is a reflexive essay based on the concept of a device proposed by Deleuze.Results: we unraveled the lines of visibility and enunciation, the lines of force and the lines of subjectivity of the health education device, highlighting the real wills implied in the modes of subjectivation produced in this device. The lines of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
25

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 18 publications
0
18
0
25
Order By: Relevance
“…24 In view of the above, multiple factors are revealed that interfere with the quality of the contraceptive care offered, so for the preparation of the scenes it was necessary to elaborate, in an improvised way, a script and, consequently, to decide for the creation of the characters, working, thus, the device of health education that encourages inventing and experimenting in an attempt to circumvent the fixed and pre-organized methods. 7 In this same direction, the Paideia method was applied by establishing dialog in the co-production and validation (or not) of the proposed actions to improve contraceptive care. Since the various actions proposed signal the desire for change in an attempt to seek the articulation of knowledge and practices; in the articulated and simultaneous conjugation of power, knowledge and affection; and in expanding the conception of the object of knowledge and intervention in the health field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 In view of the above, multiple factors are revealed that interfere with the quality of the contraceptive care offered, so for the preparation of the scenes it was necessary to elaborate, in an improvised way, a script and, consequently, to decide for the creation of the characters, working, thus, the device of health education that encourages inventing and experimenting in an attempt to circumvent the fixed and pre-organized methods. 7 In this same direction, the Paideia method was applied by establishing dialog in the co-production and validation (or not) of the proposed actions to improve contraceptive care. Since the various actions proposed signal the desire for change in an attempt to seek the articulation of knowledge and practices; in the articulated and simultaneous conjugation of power, knowledge and affection; and in expanding the conception of the object of knowledge and intervention in the health field.…”
Section: Discussionmentioning
confidence: 99%
“…25 A challenge is presented here: it is not enough to offer the adolescent (or any other user) contraceptive care actions, it is urgent to promote the protagonism of this user through educational processes in health that promote participation beyond what is put. 7 Several studies indicate that the care for adolescents, in the context of sexual and reproductive health, is precarious and not specific, 26 some also consider that the way the professionals perceive teenage pregnancy is what will influence their attitude toward prescribing contraceptive methods for adolescents; 27 others believe that increasing adolescents' access to the health services requires a reduction in formalities, besides perceiving promoting characteristics for health actions in the school. 19 For the outcome of the scenes, there was the insertion of the proposed action chosen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vitimização também é associada a dificuldades socioemocionais e inabilidades sociais (SILVA et al, 2016). Nesse sentido, a linguagem artística (corporal e verbal), proporcionada pelo teatro, pode ajudar no acesso aos níveis afetivos e emocionais dos adolescentes, auxiliando na interpretação e percepção das informações transmitidas, bem como no suporte e auxílio às vítimas (TOASSA et al, 2010;KALINOWSKI et al, 2013;FRANÇA, 2015 SOARES et al, 2017). Da mesma forma, a saúde também teve seu conceito ampliado, perdendo seu caráter biomédico de ausência de doença, para uma determinação social do processo saúde-doença que permitiu a inclusão de outros fatores intervenientes neste processo, tal como a violência, as condições socioeconômicas, entre outros (FEIO;OLIVEIRA, 2015;SOARES et al, 2017).…”
Section: Introductionunclassified
“…Nessa perspectiva, a educação em saúde se constitui por meio da construção dialogada do conhecimento, valorizando a autonomia do sujeito que é capacitado para ser responsável pelos seus determinantes de saúde (FEIO;OLIVEIRA, 2015;SOARES et al, 2017). Assim, destaca-se a necessidade da realização de estudos com práticas educativas, voltadas para os adolescentes, que abordem o bullying de forma horizontal e multidimensional, com atividades que os consideram como protagonistas da ação e valorizem o contexto de vida individual e coletiva dos participantes, atendendo, assim, às necessidades peculiares da adolescência (TOASSA et al, 2010;SOUZA, 2011;SILVA, M. et al, 2017).…”
Section: Introductionunclassified